Evaluation of surface characteristics and weight variation of different composite resins after simulated toothbrushing - De Almeida, Jéssika; Messias, Aion [UNESP]; Gadelha, Diana; Caldas, Sergei; Caldas, Marília (Thieme, 2020)
Objective: To evaluate the surface characteristics of restorations performed after simulated toothbrushing and to compare the results between the composites. Materials and Methods: In total, 80 samples were made (7 mm × 4 mm) from the composites: Bulk Fill One, Bulk Fill Flow, Z350 XT, and Z350 XT flow (3M/ESPE, St. Paul, MN, USA). Half of the specimens was submitted to 60,000 cycles of simulated toothbrushing, while the other half was the control group (n = 10). The surface was evaluated through Scanning electronic microscopy (SEM), surface roughness (Ra), and weight loss, before and after the simulated toothbrushing. To evaluate the statistical analysis, a two-factors variance test and the Tukey's posttest were performed. Results: In the analysis performed by SEM, it was observed the presence of both small and medium protruding particles in all groups after simulated toothbrushing, with the exception of the group which used Z350 flow composite. All materials presented increasing on Ra after simulated toothbrushing. Regarding weight variation, there was not any significant statistical difference in all materials. Conclusions: The abrasive process occasioned by toothbrushing leads to changes on the particles' disposition, which causes changes on the surface and increase on the Ra. On the other hand, there was not any difference regarding to weight variation.
Keywords: Scanning electronic microscopy; surface properties; wear